Nutrient and fatty acid composition of cultured and wild caught gold-spot mullet Liza parsia (Hamilton, 1822) - Syama Dayal, J.; Ambasankar, K.; Jannathulla, R.; Kumaraguruvasagam, K. P.; Kailasam, M. (Indian Journal of Fisheries, 2019)
The gold-spot mullet, Liza parsia (Hamilton, 1822) is a common mullet species that constitutes year round thriving fishery in the shallow coastal waters, estuaries, mangrove swamps and brackishwater lakes along the coast of India. Nutrient and fatty acid composition were analysed in cultured and wild caught L. parsia of different size groups. Fish were cultured with formulated pelleted feed in brackishwater pond at Nagayalanka (15.9450 N; 80.9180E), Andhra Pradesh, India. Wild samples of L. parsia were caught from the same region near Krishna River. The fishes were categorised into four size groups (150 g) from both sources. The moisture and ash content were higher (p